Evaluation of Polymeric Adsorbents for the Refining of Crude Palm Oil - Yoong, Stephen See Kin (1999)
Three types of adsorbents namely EXA 31, EXA 32 and EXA 50 were tested for their ability to refine CPO. These polymers are made up of styrene DVB copolymer without functional group and ionic form. The adsorption process was carried in packed column with temperature maintained at 50°C flowrate of 2 mlls and 70°C for flowrate of 0.1 ml/s. EXA 50 recorded the highest adsorption capacity of 0.31 mg of carotene per gram of adsorbent at this flowrate. EXA 32 and EXA 31 recorded adsorption capacity of 0.29 mg and O. 18 mg carotene per gram of adsorbent. The regeneration efficiency for EXA 31 tends to decrease with the increase in the number of runs. After five runs the regeneration efficiency was at 47.8%. The regeneration efficiency of EXA 32 initially increases but was followed by a decrease. After five runs the regeneration efficiency was at 78.2%. The regeneration efficiency of EXA 50 increases with the increase in the number of runs. This is an important finding as it indicates that the adsorbent could be used for a longer period of time without much deterioration to its adsorption capacity. Performance study for the low flow (0.1 ml/s) was carried out only on the best adsorbent EXA 50. The effect of flowrate on carotene adsorption capacity and regeneration efficiency could be determine by comparing the results for the high flow (2ml/s) and the low flow (0.1 ml/s). Carotene concentration in the hexane fraction for the 0.1 ml/s flow (17 500ppm) was 17 times higher than that in the high flow (986 ppm). The amount of carotene adsorbed per gram of adsorbent also increased by 2 5% from 0.31 mg/g to 0.39 mg/g. The regeneration efficiency also recorded improvement that was from 66.2% for the high flow to 79% for the low flow.